Prostaglandin-H-synthase isozyme expression in normal and neoplastic human skin - Müller-Decker, Karin; Krieg, Peter; Bayerl, Christiane; Marks, Friedrich; Fürstenberger, Gerhard (International journal of cancer, 1999)
Expression of prostaglandin-H-synthase (PGHS) isozymes was analyzed in 50 biopsies of normal human skin and of pre-malignant and malignant skin lesions, by means of quantitative RT-PCR, immunoprecipitation and Western blotting, as well as immunohistochemistry. Normal skin constitutively expressed PGHS-1 in all cell layers of the epidermis, in endothelial cells of small blood vessels and in sweat-gland epithelium. PGHS-2 expression was very low and restricted to a few keratinocytes of the interfollicular and follicular epidermis. Steady-state concentrations of PGHS-1 and PGHS-2 mRNA were similar in normal skin and in basal-cell carcinomas, but PGHS-1 mRNA was reduced and PGHS-2 mRNA was elevated in actinic keratoses, squamous-cell carcinomas and keratoacanthomas. PGHS-1 protein was detected in all tumor biopsies, being occasionally increased in basal-cell carcinomas. High amounts of PGHS-2 protein were found in actinic keratoses, squamous-cell carcinomas and keratoacanthomas, but not in basal-cell carcinomas. Four malignant melanomas included in this study contained PGHS-1 but no PGHS-2 protein. Immunohistochemical analysis of the biopsies identified keratinocytes, in addition to cells of inflammatory infiltrates and of dendritic morphology, as the major PGHS-expressing cell types. PGHS-2-specific signals were spread throughout the epidermal part of actinic keratoses and squamous-cell carcinomas. These data suggest that constitutive up-regulation of PGHS-2 expression is a consistent pre-malignant event in squamous-cell cancer development in man, as it is in animal models of skin carcinogenesis. Thus, pre-cancerous lesions such as actinic keratoses present a likely target for chemoprevention of skin cancer by selective PGHS-2 inhibitors.